Zirconium-based metal-organic framework for tungsten-molybdenum separation, preparation method and tungsten-molybdenum separation method
Patent Information
- Application Number
- CN202310305481.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-03-27
AI Technical Summary
目前采用吸附材料进行钨钼分离的材料以树脂材料为主,很少有合成MOF进行钨钼选择性吸附分离的研究,例如传统的D501树脂,对钨的吸附容量为332.4mg/g,对钼的吸附容量122.5mg/g,分离系数为36.9;D309树脂对钨的吸附容量为242mg/mL,对钼的吸附容量73mg/mL,分离系数达到53.3
[0028] 1. The tungsten-molybdenum separation method provided by this invention utilizes the selective adsorption of tungsten and molybdenum by zirconium-based metal-organic framework materials to achieve their separation. This not only expands the application of metal-organic framework materials but also provides a new approach for tungsten-molybdenum separation, and has significant research and application value.
Smart Images

Figure CN116497218B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorption separation materials technology, and in particular to a zirconium-based metal-organic framework material for tungsten-molybdenum separation, its preparation method, and a tungsten-molybdenum separation method. Background Technology
[0002] With the development of the electronics and electrical appliance industry, the purity requirements for tungsten and molybdenum products are becoming increasingly stringent. In molybdenum products, the control of tungsten, an impurity element, is also becoming increasingly strict. However, with the continuous depletion of high-quality molybdenum resources, the content of tungsten and other impurities in the available resources is increasing. Tungsten and molybdenum both belong to rare high-melting-point metals, located in Group VI of the periodic table. Due to the "lanthanide contraction," their atomic radii and chemical properties are very similar, and they often exist in minerals as tungstate and molybdate ions, often occurring together. Therefore, the separation of molybdenum during tungsten metallurgy has always been a key research topic for scholars both domestically and internationally.
[0003] In recent years, scholars both domestically and internationally have conducted extensive research on the adsorption and separation of tungsten and molybdenum, discovering many effective methods for their separation, such as extraction, precipitation, ion exchange, and liquid membrane separation. The separation mechanisms employed include the difference in affinity of tungsten and molybdenum for sulfur, the difference in redox potentials of tungsten and molybdenum, and the difference in affinity between thiomolybdate and tungstate ions. Extraction methods primarily rely on the differences in the chemical properties of tungsten and molybdenum. For example, separation can be achieved by utilizing the differences in properties between thiomolybdate and tungstate; by utilizing the differences in molybdenum oxide cations and tungsten oxide anions; and by utilizing the differences in the properties of peroxide complexes. The advantages are a short process, simple equipment, and low cost; the disadvantages are long separation time and excessive overall time consumption. Precipitation methods utilize the different affinities of the substances generated by the reactions of tungsten and molybdenum with different media under certain conditions to achieve the separation of tungsten and molybdenum. Its advantages are high tungsten removal rate, short processing time, and simple equipment; the disadvantages are large volume consumption, high price, and high tungsten loss. Ion exchange is a method that utilizes the difference in affinity between thiomolybdate and tungstate ions for resin to achieve the adsorption and separation of tungsten and molybdenum. The separation principle involves first subjecting the solution to a thiolation reaction. Molybdate ions undergo thiolation first, and the resin has a stronger adsorption capacity for thiomolybdate ions than for tungstate ions. During desorption, tungstate ions are desorbed first, thus achieving the separation of tungsten and molybdenum. Its advantages include a simple process, high molybdenum removal efficiency, low pollution, low cost, and low dosage. Its disadvantages include the difficulty in desorbing adsorbed thiomolybdate ions, requiring the use of strong oxidants for desorption, which makes resin regeneration difficult.
[0004] In recent years, metal-organic frameworks (MOFs), as a novel type of porous material, have attracted widespread attention due to their numerous advantages, including high specific surface area, tunable pore size, and modifiable surface. Previous studies have reported the use of MOFs as adsorbents for the adsorption and separation of metal ions, but reports on their use for the adsorption and separation of tungsten and molybdenum ions are relatively few. In 2017, Shibashis Halder et al. successfully synthesized a nickel-based MOF at room temperature and applied it to the adsorption and separation of Hg. + Theoretical calculations show that one sulfur atom of the thiocyanate group of this metal-organic framework can coordinate with up to two mercury atoms, resulting in an adsorption capacity as high as 713 mg / g. In 2021, Ahmed M. Omer et al. synthesized a cobalt-based metal-organic framework (ZIF-67) using a hydrothermal synthesis method and applied it to Cr... 6+ Adsorption of Cr was achieved by adding magnetic Fe3O4 to the ZIF-67 framework, followed by at least seven consecutive extractions using the same MOF. 6+ Subsequently, all showed good recyclability. Its recyclability for Cr... 6+ The maximum adsorption capacity is 119.05 mg / g. Currently, resin materials are the main adsorbents used for the separation of tungsten and molybdenum, and there is little research on the selective adsorption and separation of tungsten and molybdenum using synthetic MOFs. For example, the traditional D501 resin has an adsorption capacity of 332.4 mg / g for tungsten and 122.5 mg / g for molybdenum, with a separation coefficient of 36.9; the D309 resin has an adsorption capacity of 242 mg / mL for tungsten and 73 mg / mL for molybdenum, with a separation coefficient reaching 53.3. Therefore, using MOF materials as adsorption and separation materials for tungsten and molybdenum has application potential. Summary of the Invention
[0005] The purpose of this invention is to provide a zirconium-based metal-organic framework material for tungsten-molybdenum separation, its preparation method, and a tungsten-molybdenum separation method. By using a zirconium-based metal-organic framework material to selectively adsorb tungsten and molybdenum, the two materials can be separated efficiently. This not only expands the application of metal-organic framework materials but also provides a new and effective approach for tungsten-molybdenum separation, which is of great significance to research in this field.
[0006] To achieve the above objectives, this invention provides a method for separating tungsten and molybdenum, employing a zirconium-based metal-organic framework (MOF) for the selective adsorption and separation of tungsten and molybdenum. MOFs, as novel porous materials, have relatively mature structures and preparation methods, but their application in the selective adsorption and separation of tungsten and molybdenum is currently lacking. Different metal sites and organic ligands can endow them with different functionalities. This invention has discovered that zirconium-based MOFs exhibit excellent selective adsorption of tungsten and molybdenum. Utilizing their superior adsorption capacity for molybdenum compared to tungsten, the two materials can be separated, providing a new approach for tungsten-molybdenum separation with significant research and application value.
[0007] Furthermore, the zirconium-based metal-organic framework material uses zirconium as the central adsorption site and organic carboxylic acids as ligands; such metal-organic framework materials exhibit superior selective adsorption of tungsten and molybdenum.
[0008] Preferably, the organic carboxylic acid includes one or more of terephthalic acid, trimethyl dicarboxylate, dimethyl biphenyl ester, and pyromellitic acid, with terephthalic acid being the most preferred.
[0009] Furthermore, the tungsten-molybdenum separation method includes: placing the zirconium-based metal-organic framework material in a solution containing molybdate and tungstate for adsorption separation, wherein the adsorption capacity of the zirconium-based metal-organic framework material for molybdate is greater than its adsorption capacity for tungstate; preferably, the adsorption environment temperature is 20-30℃, the adsorption time is 1-5h, the adsorption method is an oscillation method, and the oscillation frequency is 100-200 rpm.
[0010] Preferably, the separation coefficient of the zirconium-based metal-organic framework material for tungsten and molybdenum is ≥35, more preferably ≥45. This invention utilizes a zirconium-based metal-organic framework material for the selective adsorption of molybdenum and tungsten, achieving a high separation coefficient, thus making it suitable for the separation of molybdenum and tungsten. While the separation coefficient varies slightly with changes in preparation parameters using conventional zirconium-based metal-organic framework materials, it remains at a high level.
[0011] Furthermore, the zirconium-based metal-organic framework material exhibits an adsorption capacity of ≥150 mg / g for molybdate, preferably ≥250 mg / g; and an adsorption capacity of ≤20 mg / g for tungstate, preferably ≤16 mg / g. By adjusting the preparation parameters of the zirconium-based metal-organic framework material, the adsorption capacity and separation coefficient can be controlled, thereby achieving a better separation effect.
[0012] To achieve the above objectives, the present invention also provides a method for preparing a zirconium-based metal-organic framework material for use in any of the above-described tungsten-molybdenum separation methods, comprising: using a zirconium salt as a metal source, an organic carboxylic acid as an organic ligand, and N,N-dimethylformamide as a reaction solvent, and preparing the zirconium-based metal-organic framework material by a solvothermal method.
[0013] Furthermore, the zirconium salt includes zirconium tetrachloride; the organic carboxylic acid includes one or more of terephthalic acid, trimethyl dicarboxylate, dimethyl biphenylcarboxylate, and pyromellitic acid.
[0014] Preferably, the preparation method further includes the addition of hexadecyltrimethylammonium bromide.
[0015] Furthermore, the molar ratio of the zirconium salt to the organic carboxylic acid is 1:(1-2), preferably 1:2;
[0016] And / or, the molar ratio of the zirconium salt to the hexadecyltrimethylammonium bromide is 1:(0.8-1.2), preferably 1:1;
[0017] And / or, the crystallization temperature of the solvothermal method is 80℃-180℃, preferably 130℃-180℃; the time is 5-48h, preferably 20-30h.
[0018] Furthermore, the preparation method includes:
[0019] Zirconium salt and organic carboxylic acid were added to N,N-dimethylformamide, and hydrochloric acid was added dropwise while stirring. Then, an N,N-dimethylformamide solution containing hexadecyltrimethylammonium bromide was added. Next, a crystallization reaction was carried out at 80℃-180℃. After crystallization, solid-liquid separation, washing, drying and activation were carried out in sequence to obtain zirconium-based metal-organic framework materials.
[0020] Furthermore, the activation includes: heat treatment in a muffle furnace at 160°C; or heat treatment in a vacuum drying oven at 80°C-110°C, preferably in a vacuum drying oven at 110°C. Heat treatment activation removes residual solvent from the pores of the adsorbent material, thereby increasing its specific surface area and adsorption capacity.
[0021] Furthermore, the drying temperature is 80℃-100℃, and the time is 2-8 hours;
[0022] And / or, the washing includes washing with N,N-dimethylformamide and deionized water in sequence.
[0023] This invention provides zirconium-based metal-organic framework adsorbents prepared at different crystallization temperatures, with different activation methods, and with different molar ratios of ZrCl4 to terephthalic acid.
[0024] In some specific embodiments, the preparation method includes the following steps:
[0025] First, pour 25 mL of N,N-dimethylformamide (DMF) into a beaker as a solvent. Then, add ZrCl4 and terephthalic acid in a ratio of 1:1 to 1:2 to the beaker containing the solvent and stir thoroughly to dissolve. While stirring, add a certain amount of HCl dropwise to the beaker containing the mixed solution. In another beaker, add 10 mL of N,N-dimethylformamide (DMF) and a certain amount of hexadecyltrimethylammonium bromide (CTAB) as a complexing agent to the DMF. Stir thoroughly to dissolve. After dissolution, pour the solution into the beaker containing the 25 mL DMF and mix thoroughly. Then, transfer the solution from the beaker to a 50 mL polytetrafluoroethylene-lined reactor. Place the reactor in an electrically heated drying oven for crystallization at 80-180℃. After crystallization, separate by filtration and wash three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated to remove residual solvent in the pores of the adsorbent material. The activation method is to heat at 160℃ in a muffle furnace or at 80℃-110℃ in a vacuum drying oven. The resulting white powder is the zirconium-based metal-organic framework adsorbent.
[0026] To achieve the above objectives, the present invention also provides a zirconium-based metal-organic framework material for tungsten-molybdenum separation, which is prepared by any of the preparation methods described above.
[0027] The beneficial effects of this invention are as follows:
[0028] 1. The tungsten-molybdenum separation method provided by this invention utilizes the selective adsorption of tungsten and molybdenum by zirconium-based metal-organic framework materials to achieve their separation. This not only expands the application of metal-organic framework materials but also provides a new approach for tungsten-molybdenum separation, and has significant research and application value.
[0029] 2. The zirconium-based metal-organic framework material for tungsten-molybdenum separation provided by the present invention uses zirconium as the central adsorption site and organic carboxylic acid as the ligand, preferably terephthalic acid. The raw materials are readily available and the preparation method is simple, thus it has high practicality and economic value.
[0030] 3. The present invention preferably prepares zirconium-based metal-organic framework materials by a solvothermal method and activates them by heat treatment to remove residual solvent in the pores, thereby increasing their specific surface area and adsorption capacity to achieve better adsorption and separation effects. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0032] Figure 1 This is a flowchart of the synthesis method of the adsorbent material of the present invention.
[0033] Figure 2 The XRD pattern is shown for the adsorbent prepared in Example 8.
[0034] Figure 3 This is a SEM image of the adsorbent prepared in Example 8.
[0035] Figure 4 The images show the FT-IR spectra of the adsorbent prepared in Example 8 before and after adsorption. Detailed Implementation
[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention are described clearly and completely below. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0037] Example 1
[0038] The preparation process of this invention is as follows: Figure 1 As shown, 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 2 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:2) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution in the beaker was then transferred to a 50 mL polytetrafluoroethylene-lined reactor, which was crystallized at 80 °C for 24 h. After crystallization, the mixture was separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a muffle furnace at 160℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0039] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0040] The zirconium-based metal-organic framework material has an adsorption capacity of 164.6 mg / g for molybdenum and 16.3 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 41.5.
[0041] Example 2
[0042] 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 2 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:2) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined reactor and crystallized at 130 °C for 24 h. After crystallization, the mixture was separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a muffle furnace at 160℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0043] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0044] The zirconium-based metal-organic framework material has an adsorption capacity of 181.4 mg / g for molybdenum and 13.8 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 46.3.
[0045] Example 3
[0046] 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 2 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:2) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined reactor and crystallized at 180 °C for 24 h. After crystallization, the crystals were separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a muffle furnace at 160℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0047] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0048] The zirconium-based metal-organic framework material has an adsorption capacity of 219.4 mg / g for molybdenum and 11.6 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 52.3.
[0049] As can be seen from Examples 1-3, the zirconium-based metal-organic framework materials prepared in this invention exhibit high separation coefficients for both molybdenum and tungsten. Specifically, the separation coefficient and the adsorption capacity for molybdenum gradually increase with increasing crystallization temperature. This demonstrates that the adsorption and separation of molybdenum and tungsten can be achieved using zirconium-based metal-organic framework materials.
[0050] Example 4
[0051] 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 1 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:1) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined reactor and crystallized at 80 °C for 24 h. After crystallization, the crystals were separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a muffle furnace at 160℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0052] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0053] The zirconium-based metal-organic framework material has an adsorption capacity of 162.1 mg / g for molybdenum and 18.7 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 39.6.
[0054] Example 5
[0055] 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 1 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:1) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined reactor and crystallized at 130 °C for 24 h. After crystallization, the mixture was separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a muffle furnace at 160℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0056] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0057] The zirconium-based metal-organic framework material has an adsorption capacity of 191.6 mg / g for molybdenum and 14.2 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 43.8.
[0058] Example 6
[0059] 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 1 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:1) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined reactor and crystallized at 180 °C for 24 h. After crystallization, the mixture was separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a muffle furnace at 160℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0060] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0061] The zirconium-based metal-organic framework material has an adsorption capacity of 292.6 mg / g for molybdenum and 15.7 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 49.8.
[0062] As can be seen from Examples 4-6, when the crystallization temperature is the same, the molar ratio of ZrCl4 to terephthalic acid is 1:2, resulting in a larger separation coefficient and greater adsorption capacity for molybdenum.
[0063] Example 7
[0064] 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 2 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:2) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined reactor and crystallized at 180 °C for 24 h. After crystallization, the crystals were separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a vacuum drying oven at 80℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0065] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0066] The zirconium-based metal-organic framework material has an adsorption capacity of 208.8 mg / g for molybdenum and 12.6 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 40.1.
[0067] As can be seen from Examples 7 and 3, the activation effect of the vacuum drying oven at 80°C is lower than that of the muffle furnace at 160°C.
[0068] Example 8
[0069] 25 mL of N,N-dimethylformamide (DMF) was poured into a beaker as a solvent. Then, 1 mmol of ZrCl4 and 2 mmol of terephthalic acid (ZrCl4 to terephthalic acid molar ratio of 1:2) were added to the beaker containing the solvent and stirred thoroughly to dissolve. Then, 0.44 mL of HCl was added dropwise to the beaker containing the mixed solution while stirring. In another beaker, 10 mL of N,N-dimethylformamide (DMF) was added, and 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added as a complexing agent. The mixture was stirred thoroughly to dissolve, and then poured into the beaker containing the 25 mL DMF, ensuring thorough mixing. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined reactor and crystallized at 180 °C for 24 h. After crystallization, the crystals were separated by filtration and washed three times with DMF solution and deionized water, respectively. Then, the product is dried at 100℃ for 6 hours to remove moisture. Finally, it is activated in a vacuum drying oven at 110℃ to remove residual solvent in the pores of the adsorbent material. The resulting white powder is the zirconium-based metal-organic framework material.
[0070] The prepared zirconium-based metal-organic framework adsorbent was tested for its tungsten-molybdenum adsorption and separation performance. Sodium tungstate and sodium molybdate were used as the tungsten and molybdenum sources, respectively, to prepare a tungsten-molybdenum mixed solution with a molar ratio of 1:1. The adsorption environment temperature was 20-30℃, the adsorption time was 3 hours, and the adsorption method was an oscillation method with an oscillation frequency of 150 rpm. After adsorption, the adsorption capacity of the adsorbent for tungsten and molybdenum and the tungsten-molybdenum separation coefficient were measured and calculated.
[0071] The structure and morphology of this zirconium-based metal-organic framework material are as follows: Figure 2-3 As shown, this invention successfully prepared a zirconium-based metal-organic framework material. This zirconium-based metal-organic framework material exhibits an adsorption capacity of 355.6 mg / g for molybdenum and 20.2 mg / g for tungsten, with a molybdenum-tungsten separation coefficient of βMo / W = 51.4. From... Figure 4 As can be seen, the characteristic peak of molybdenum-oxygen bonds is generated after adsorption, indicating that molybdate ions were successfully adsorbed.
[0072] As can be seen from Examples 7 and 8, the activation effect of a vacuum drying oven at 110°C is far superior to that of a vacuum drying oven at 80°C and a muffle furnace at 160°C. This indicates that vacuum drying is more effective at removing solvents and does not damage the framework structure due to excessively high temperatures. Therefore, this invention, through activation treatment, helps to improve the adsorption capacity and selective adsorption and separation effect of zirconium-based metal-organic framework materials.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for separating tungsten and molybdenum, characterized in that, Selective adsorption and separation of tungsten and molybdenum were achieved using zirconium-based metal-organic framework materials. The method for preparing the zirconium-based metal-organic framework material includes: adding zirconium salt and organic carboxylic acid to N,N-dimethylformamide, and adding hydrochloric acid dropwise while stirring; then adding an N,N-dimethylformamide solution containing hexadecyltrimethylammonium bromide; then carrying out a crystallization reaction at 80℃-180℃; after crystallization, performing solid-liquid separation, washing, drying, and activation in sequence to obtain the zirconium-based metal-organic framework material. The zirconium salt includes zirconium tetrachloride; the organic carboxylic acid includes one or more of terephthalic acid, trimethyl dicarboxylate, dimethyl biphenyl ester, and pyromellitic acid. The molar ratio of the zirconium salt to the organic carboxylic acid is 1:(1-2); The molar ratio of the zirconium salt to the hexadecyltrimethylammonium bromide is 1:(0.8-1.2). The crystallization time is 5-48 hours; The activation includes: heat treatment in a vacuum drying oven at 110°C.
2. The tungsten-molybdenum separation method according to claim 1, characterized in that, The tungsten-molybdenum separation method includes: placing the zirconium-based metal-organic framework material in a solution containing molybdate and tungstate for adsorption separation, wherein the adsorption capacity of the zirconium-based metal-organic framework material for molybdate is greater than its adsorption capacity for tungstate.
3. The tungsten-molybdenum separation method according to claim 2, characterized in that, The zirconium-based metal-organic framework material has a separation coefficient of ≥35 for tungsten and molybdenum. And / or, the zirconium-based metal-organic framework material has an adsorption capacity of ≥150 mg / g for molybdate and an adsorption capacity of ≤20 mg / g for tungstate.
4. A method for preparing a zirconium-based metal-organic framework material for use in the tungsten-molybdenum separation method according to any one of claims 1-3, characterized in that, include: Zirconium salt and organic carboxylic acid were added to N,N-dimethylformamide, and hydrochloric acid was added dropwise while stirring. Then, an N,N-dimethylformamide solution containing hexadecyltrimethylammonium bromide was added. Next, a crystallization reaction was carried out at 80℃-180℃. After crystallization, solid-liquid separation, washing, drying and activation were carried out in sequence to obtain zirconium-based metal-organic framework materials. The zirconium salt includes zirconium tetrachloride; the organic carboxylic acid includes one or more of terephthalic acid, trimethyl dicarboxylate, dimethyl biphenyl ester, and pyromellitic acid. The molar ratio of the zirconium salt to the organic carboxylic acid is 1:(1-2); The molar ratio of the zirconium salt to the hexadecyltrimethylammonium bromide is 1:1; The crystallization time is 5-48 hours; The activation includes: heat treatment in a vacuum drying oven at 110°C.
5. The method for preparing zirconium-based metal-organic framework materials for tungsten-molybdenum separation according to claim 4, characterized in that, The drying temperature is 80℃-100℃, and the time is 2-8 hours; And / or, the washing includes washing with N,N-dimethylformamide and deionized water in sequence.
6. A zirconium-based metal-organic framework material for tungsten-molybdenum separation, characterized in that, It is prepared using the preparation method described in claim 4 or 5.
Citation Information
Patent Citations
Metal-organic framework UiO-66 adsorbent and modified material thereof
CN108671892A